Studi Literatur Determinan Perilaku Makan Sayur Dan Buah Pada Remaja Menurut Teori Kognitif Sosial Tahun 2021 - 2025 - Maudy Mutiarahman; Luqman Effendi (Barongko: Jurnal Ilmu Kesehatan, 2026)
Adolescence is the transition from childhood to adulthood, a period between childhood and adulthood, characterized by social, mental, and physical changes. Physical growth in teenagers is shown by sharp increases in height and weight. You should consume plenty of fruits and vegetables to maintain your body's nutritional balance. Many vitamins, minerals, and fibers needed by the body are found in this type of diet every day. Teenagers often skip meals, snack, and consume a lot of fast food, along with other poor eating behaviors. These issues can affect teenagers' health in the future, According to the World Health Organization (WHO), 400–600 grams of fruits and vegetables per day are recommended for adolescents. Schools are expected to teach adolescents about a balanced diet. Understanding nutrition affects attitudes and behavior when making food choices, which in turn influences eating patterns and nutritional status. Problems in adolescent growth and development as well as eating behavior issues will arise due to ignorance about the nutritional contributions of various types of foods. A literature review on the topic or variable being studied is used in this study. The information used comes from the researcher's own literature review and research articles that discuss the topic. Variables that influence the Determinants of Fruit and Vegetable Eating Behavior in Adolescents According to Social Cognitive Theory 2021 – 2025.